Pengaruh Manajemen Laba Dan Perencanaan Pajak Terhadap Nilai Perusahaan Dengan Good Corporate Governance Sebagai Variabel Moderasi - Ilham Aulia Hendra; Erinos NR (Jurnal Eksplorasi Akuntansi, 2020)
This research investigate the effect of Earning Manajement and Tax Planning on Corporate Value in Consumer Good companies listed on the Indonesia Stock Exchange in 2014-2018. The type of this research is associative. The population in this study were all consumer good companies listed on the Indonesia Stock Exchange in 2014-2018, and the sample was determined using the purposive sampling method, with 16 sample from 57 consumer good companies. Multiple reggression was used to analysis the data. The result shows that earning management have a negative effect on corporate value. Tax planning have a negative effect on corporate value. Good Corporate Governance cannot moderate the relationship between earning management and tax planning to corporate value.